Topical Steroids and CO2 Laser in the Treatment of Refractory Oral Lichenoid Drug Reaction and Lichenoid Contact Lesion: a Case Report - Kobkan Thongprasom; Somchai Sessririsombat; Kanjana Singkharotai; Achara Vathanasanti; Keskanya Subbalek (Acta Stomatologica Croatica, 2014)
A 54-year-old female presented with severe pain on the gingiva and buccal mucosa. Oral findings revealed generalized fiery red gingiva, ulcerative with white striae covered by pseudo-membranes on both buccal mucosae. She had hypertension, dyslipidemia, subclinical hypothyroidism and arthritis. She was treated with atorvastatin, hydrochlorothiazide, valsartan, levothyroxine and non-steroidal anti-inflammatory drug (NSAIDs). Her oral lesions were a slight improvement from a previous treatment with pimecrolimus cream, triamcinolone acetonide 0.1% orabase and injection. After diclofenac was replaced with tenoxicam and oral lesions were treated with various topical steroids, the lesions showed marked improvement. The biopsy from the buccal mucosa revealed oral lichen planus. Patch test showed positivity to mercury, gold sodium thiosulfate and palladium. One year later the left buccal mucosa showed red, round papillomatous-like lesions. The histopathological report showed a non-specific ulcer with chronic inflammation. The lesions flared up after replacing amalgam with crowns. After CO2 laser treatment, the lesions showed some improvement. Direct and indirect immunofluorescence of the lesions proved to be negative. This first case report showed that the palliative treatment of refractory oral lichenoid lesions with potent topical steroids for 7 years had no side-effects. CO2 laser can be an alternative treatment of refractory lesion in this case.